Análise dos fatores prognósticos da cirurgia para correção de fratura de quadril em pacientes idosos internados em um hospital do Sistema Único de Saúde do sul do Brasil - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
Introduction: With the aging of the world population, diseases such as osteoporosis and sarcopenia have a high incidence, with a consequent increase in complications such as falls and hip fractures, leading to an increase in morbidity and mortality and medical costs for the treatment of these fractures. The objective of this study is to evaluate the prognostic factors related to the surgical treatment of hip fractures in elderly patients. Method: This is a retrospective cohort study with patients admitted to a regional university hospital in Paraná. A medical record review was carried out on patients hospitalized between January and June 2024 for hip fractures, who underwent tomography within the first 72 hours of admission and underwent a surgical procedure. Result: The study presented N of 53 patients, 13 male and 40 female, 1 patient of Asian ethnicity, 4 brown patients and the rest Caucasian. The average age of the patients was 77 years, and only 5 patients had muscle mass assessed by tomography above the reference value. Only 25 patients (47.16%) were able to sustain the body load on the surgically treated limb at the time of discharge from the hospital. Of the prognostic factors evaluated, only the Barthel index, strength assessment by dynamanometry and the ability to walk without assistance before fracture showed a moderate and significant correlation with the ability to bear weight. Age, BMI, SMA, SMI, days between fracture and correction surgery, presence of systemic arterial hypertension, presence of diabetes mellitus, presence of dyslipidemia, presence of heart failure, and presence of chronic obstructive pulmonary disease did not show a significant correlation. Discussion: It is necessary to improve the selection of elderly patients with hip fractures who may benefit from invasive surgical treatment. High-cost exams such as computed tomography to assess muscle mass did not show a correlation with therapeutic success, to the point that strength assessment using dynamometry, functional assessment using the Barthel scale and questions about ambulation prior to the fracture had a moderate and significant correlation. These low-cost and simple technology methods can be readily used, not to replace the medical decision shared with the patient but to provide support for a free and informed decision.
Keywords: Fratura de quadril; Idoso; Prognóstico; Ciências da Saúde